Delegation, worker compensation, and strategic competition - Werner Güth; Kerstin Pull; Manfred Stadler (University of Tübingen, Faculty of Economics and Social Sciences, 2014)
We study interfirm competition on a product market where effort decisions are delegated to the firms' workers. Intrafirm organization is captured by a principal-multiagent framework where firm owners implement alternative compensation schemes for the workers. We show that the value of delegation as well as the optimal design of the compensation scheme crucially depend on the intensity of competition. In particular, our model explains why piece rates and performance-based revenue sharing may be observed in different markets at the same time.
urn:nbn:de:bsz:21-opus-72069
Keywords: C72; L22; M52; 330; delegation; agency theory; compensation schemes